UI/UX Design for Web-Based Syshoe Information System Using Design Thinking Approach - Felda Alvian Firifki; Dwi Hosanna Bangkalang (Universitas Islam Indragiri, 2026)
This study aims to design the UI/UX of the Syshoe web-based information system to improve service efficiency, expand market reach through digital media, and facilitate online ordering by providing users with more comprehensive information. The UI/UX design of the Syshoe information system was developed using the Design Thinking method to ensure that the system aligns with user needs and delivers a more effective user experience. The design process resulted in both low-fidelity and high-fidelity prototypes tailored to user requirements, which were subsequently evaluated using the System Usability Scale (SUS). The findings indicate that the UI/UX design of the Syshoe information system achieved an acceptable usability category, with a final SUS score of 79.7 from user evaluations and 80.8 from administrator evaluations. These results demonstrate that the system is feasible, comfortable, and effective for both users and administrators. Therefore, this study is expected to serve as a reference for the development of similar systems, particularly for MSMEs seeking to adopt digital transformation initiatives.